2018
DOI: 10.1007/s00285-018-1232-z
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive correlations between seed size and germination time

Abstract: We present a model for the coevolution of seed size and germination time within a season when both affect the ability of the seedlings to compete for space. We show that even in the absence of a morphological or physiological constraint between the two traits, a correlation between seed size and germination time is nevertheless likely to evolve. This raises the more general question to what extent a correlation between any two traits should be considered as an a priori constraint or as an evolved means (or "in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It has been noted that seed size is positively correlated with GP and seedling growth [27]. However, it was also reported that seed size is not significantly correlated with germination [28].…”
Section: The Influence Of Biological Characters On H Chinensis Seed G...mentioning
confidence: 98%
“…It has been noted that seed size is positively correlated with GP and seedling growth [27]. However, it was also reported that seed size is not significantly correlated with germination [28].…”
Section: The Influence Of Biological Characters On H Chinensis Seed G...mentioning
confidence: 98%
“…It continues to investigate the correlations between the different indicators that can characterize the quality of the seeds. In adaptive correlations between seed size and germination time [71], present a model for the coevolution of seed size and germination time within a season when both affect the ability of the seedlings to compete for space and show that even in the absence of a morphological or physiological constraint between the two traits, a correlation between seed size and germination time is nevertheless likely to evolve.…”
Section: Adnormentioning
confidence: 99%
“…Seed size, similar to other functional traits, affects population persistence and post-germination traits, and has been shown to be under strong natural selection (Larios et al, 2014; Larios and Venable., 2018). Studies on the implications of the variation in seed size have indicated that being larger can result in producing larger and more vigorous seedlings than smaller ones (Geritz et al, 2018), putting large-seeded species at a competitive advantage by preventing the growth of seedlings that emerge later. It has been shown that the fitness advantage of larger seeds over smaller ones is related to a higher likelihood of avoiding unfavorable conditions by lower persistence in the soil seed bank (Leishman et al, 2000).…”
Section: Introductionmentioning
confidence: 99%